1991
DOI: 10.1016/s0022-5347(17)38503-8
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Human Urothelial Carcinoma Based on Nuclear Atypia and Mitotic Frequency. II. Histological Description

Abstract: A grading system was applied in a retrospective study of 124 patients with transitional cell carcinoma of the bladder using a modified Bergkvist system. The intermediate World Health Organization (WHO) grade II tumors were divided into supposedly benign and malignant forms of grades IIa and IIb, respectively. The 5-year survival was 92% for patients with grade IIa urothelial carcinoma, compared to 43% for patients with grade IIb tumors. The corresponding figures for grades I and III tumors were 100 and 44%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
13
0
3

Year Published

1992
1992
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 9 publications
8
13
0
3
Order By: Relevance
“…In univariate survival analysis the fraction of PCNA/cyclin positive nuclei predicted survival significantly like other histoquantitative methods (Blomjous et al, 1989;Lipponen et al, 1990a;1991a,b;Carbin et al, 1991). The results in papillary tumours were comparable to those from other quantitative methods (Lipponen et al, 1991a,b) whereas in superficial tumours PCNA/cyclin positivity was superior to morphometric methods in predicting survival.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In univariate survival analysis the fraction of PCNA/cyclin positive nuclei predicted survival significantly like other histoquantitative methods (Blomjous et al, 1989;Lipponen et al, 1990a;1991a,b;Carbin et al, 1991). The results in papillary tumours were comparable to those from other quantitative methods (Lipponen et al, 1991a,b) whereas in superficial tumours PCNA/cyclin positivity was superior to morphometric methods in predicting survival.…”
Section: Discussionmentioning
confidence: 60%
“…In accor- Progression of TCC was related to fraction of nuclei positive for PCNA/cyclin. However, PCNA/cyclin positivity was inferior to mitotic frequency or flow cytometric variables (Lipponen et al, 1990b(Lipponen et al, , 1991cCarbin et al, 1991) in predicting progression since we could not establish independent predictive value for PCNA/cyclin in a multivariate analysis. Particularly in superficial tumours PCNA/cyclin was inferior to other proliferation indices in predicting progression (Lipponen et al, 1990b(Lipponen et al, , 1991c.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, a number of two-grade systems have been presented for TCC that are based on flow cytometry [20, 21, 22]or morphometry [22]. Carbin et al [23]presented a modified Bergkvist grading system, including subjective and quantitative elements, which correlated well with the prognosis. Malmström et al [21]combined flow cytometric data and the results from blood group immunohistochemistry into a new grading system for TCC.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder tumor proliferation has been extensively studied by assessment of the mitotic index [19], BrdUrd binding [20], flow cytometry [21], Ki67 labelling index on fresh nonfixed sections [20], and PCNA labelling index on fixed section [22]. Most of these studies have demonstrated a relationship between proliferation and tumor grade, stage and progression [19, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have demonstrated a relationship between proliferation and tumor grade, stage and progression [19, 23]. However, tumor proliferation was still not taken into account in the classical management of bladder tumors.…”
Section: Discussionmentioning
confidence: 99%